A Priori Problems with the Metaphysical and Causal Reduction of Consciousness - Vaghela, Kamarajsinh (Tattva Journal of Philosophy, 2021)
Consciousness exists, or so it seems to us most of the time. However, consciousness is unlike your car-keys or your cell-phone in that it is not located at a specific point in space and time. The applicability of physical laws like gravity seem moot at best when it comes to consciousness. What is desirable is an explanation of consciousness that allows it to exist and be part of the very same reality as the car-key or the cell-phone, a ‘philosophy of immanence’ as Gilles Deleuze would put it. I prefer a view that construes consciousness as causally-efficacious (having material effects upon one’s body in real time) and metaphysically separate from the brain. In essence, to say that the mind is metaphysically separate from the brain is to deny the proposition that there is nothing more to our subjective experience of mind than the mere activity of the physical brain. This paper looks at a view proposed by John Searle and tries to show that there are empirical problems with a consciousness that is causally inefficacious (unable to cause material changes) and metaphysically identical (not separate from the brain).